(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted to evaluate the efficacy of three alcoholic extracts of ginger, cloves and rue with concentrations ranging from 500 to 3000 ppm against Penicillium digitatum isolated from infected orange fruits. The concentrations of alcoholic extracts showed effectiveness against pathogenic fungi. Ginger, cloves, and rue at a concentration of ppm 3000 showed inhibition of the fungus on Potato Dextrose Agar by 77.55%, 85.00%, and 95.55%, respectively. These extracts, at the same concentration, also showed the ability to inhibit the germination of spores and reduce the lengths of germination tubes. The percentage of germinated spores reached In the alcoholic extracts of ginger, cloves and rue after 19 hours of incubation at a temperature of 2 ± 25 C 38.00%, 17.00% and 9.33%, respectively, these extracts also reduced the lengths of germination tubes to µm 5.3, µm22, µm27.0, respectively.